Imagining the nation in nature : landscape preservation and German identity, 1885-1945 - Lekan, Thomas M. (Harvard University Press, 2004)
One of the most powerful nationalist ideas in modern Europe is the assertion that there is a link between people and their landscape. Focusing on the heart of German romanticism, the Rhineland, Thomas Lekan examines nature protection activities from Wilhelmine Germany through the end of the Nazi era to illuminate the relationship between environmental reform and the cultural construction of national identity. In the late nineteenth century, anxieties about national character infused ecological concerns about industrialization, spurring landscape preservationists to protect the natural environment. In the Rhineland's scenic rivers, forests, and natural landmarks, they saw Germany as a timeless and organic nation rather than a recently patchworked political construct. Landscape preservation also served conservative social ends during a period of rapid modernization, as outdoor pursuits were promoted to redirect class-conscious factory workers and unruly youth from "crass materialism" to the German homeland. Lekan's examination of Nazi environmental policy challenges recent work on the "green" Nazis by showing that the Third Reich systematically subordinated environmental concerns to war mobilization and racial hygiene. This book is an original contribution not only to studies of national identity in modern Germany but also to the growing field of European environmental history. Table of Contents: Introduction 1. Nature's Homelands: The Origins of Landscape Preservation, 1885-1914 2. The Militarization of Nature and Heimat, 1914-1923 3. The Landscape of Modernity in theWeimar Era 4. From Landscape to Lebensraum: Race and Environment under Nazism 5. Constructing Nature in the Third Reich Conclusion Abbreviations Notes Sources Acknowledgments Index Writing squarely within the idiom of the 'invented tradition' and the 'imagined nation, ' Thomas Lekan argues that in the wake of belated unification and at a time of rapid industrialization, the German landscape came to be seen as a touchstone of national identity. He questions the idea that those engaged in landscape preservation were simply 'antimodern, ' and he challenges both scholars who have seen a straightforward continuity from pre-1933 preservationist sentiment to Nazism and those who have made exaggerated claims for the Third Reich as the progenitor of modern green politics. This is a welcome contribution to the literature on local and national identity, joining works by Celia Applegate and Alon Confino, and on the environmental history of modern Germany. Both scholarly and original, Imagining the Nation in Nature is an impressive achievement.--David Blackbourn, Harvard UniversityThis important and timely book contributes to our understanding of German identity as well as to modern concepts of environmentalism and nature. Lekan's valuable contribution elucidates the modern, technocratic, and therapeutic vision of preservation that linked Weimar and the Third Reich. His analysis of Nazi bio-nature is significant and thought-provoking.--Alon Confino, University of Virginia